Analysis of the Growth Potential of Culinary MSMEs in Tanjungpinang City - Bayti, Nur; Febrianti, Tiara; Ilham, Edinur; Jintar, Catri; Iranita, Iranita; Wulandari, Kiki (Journal La Sociale, 2025)
The main purpose of this research is to uncover the opportunities and obstacles faced by small and medium culinary businesses in Tanjungpinang City. This study uses a qualitative approach to collect data through direct observation, interviews with business actors, and document studies. The data used came from primary sources (interview results, observations) and secondary sources (literature, statistical data). The results of the study show that a strategic business location is very important for the success of the culinary business. An easily accessible location not only increases the number of customers, but also provides a competitive advantage over competitors. The increase in the number of tourists in Tanjungpinang has a positive impact on the development of the culinary business. Tourists who come are looking for a unique and varied culinary experience. SWOT analysis is used to identify internal and external factors that affect the development of culinary MSMEs in Tanjungpinang. The results of the analysis show that external factors have a higher weight.